Finite element models can reproduce the effect of nucleotomy on the multi-axial compliance of human intervertebral discs. Issue 13 (2nd October 2020) - Stadelmann, Marc A.; Stocker, Roland; Maquer, Ghislain; Hoppe, Sven; Vermathen, Peter; Alkalay, Ron N.; Zysset, Philippe K.
Abstract: Finite element (FE) models can unravel the link between intervertebral disc (IVD) degeneration and its mechanical behaviour. Nucleotomy may provide the data required for model verification. Three human IVDs were scanned with MRI and tested in multiple loading scenarios, prior and post nucleotomy. The resulting data was used to generate, calibrate, and verify the FE models. Nucleotomy increased the experimental range of motion by 26%, a result reproduced by the FE simulation within a 5% error. This work demonstrates the ability of FE models to reproduce the mechanical compliance of human IVDs prior and post nucleotomy.